EFEKTIFITAS MODUL DAN AUDIO VISUAL TERHADAP PENGETAHUAN TENTANG DETEKSI KANKER SERVIKS MELALUI METODE IVA PADA WUS SUKU TERASING DI WILAYAH KERJA PUSKESMAS TAMILOUW KABUPATEN MALUKU TENGAH - Denicell Paulina Tetelepta; Rigoan Malawat; Joula Timisela (Pusat Penelitian dan Pengabdian Kepada Masyarakat Poltekkes Kemenkes Maluku, 2021)
Background: Cervical cancer is a type of cancer that 99.7% is caused by the oncogenic human papilloma virus (HPV), which attacks the cervix. The groups at risk for cervical cancer are women of childbearing age who engage in sexual activity at an early age, have many children and have poor reproductive health behavior. The habit of changing sexual partners is one of the main factors in transmitting the HPV virus. One of the